Early life stress of infants in the SPRING home visits intervention promoting child growth and development in rural India (SPRING-ELS): development of stress measures for administration at scale. (23rd February 2017) - Bhopal, Sunil; Verma, Deepali; Divan, Gauri; Hill, Zelee; Barlow, Jane; Roy, Reetabrata; Kirkwood, Betty
Abstract: Background: SPRING-ELS (Early Life Stress) is a substudy of the SPRING cluster randomised controlled trial that is assessing a home visits programme in rural India promoting early child development and growth. Early life stress interferes with healthy child development so our aim was to evaluate its role in the SPRING causal pathway. We report findings from the preparatory phase of SPRING-ELS. Methods: To develop an explanatory model of early life stress in the community, 45 mothers of children under 2 years old took part in eight focus group discussions. To determine potential barriers to sampling, in-depth interviews were done with five mothers and two barbers (to understand cultural beliefs about young children's hair). In addition, five focus group discussions were done with mothers, grandmothers, and barbers. Salivary and hair cortisol (to assess diurnal rhythm and chronic stress) were measured in 13 children aged 11–13 months. The SPRING trial is registered withClinicalTrials.gov, numberNCT02059863 . Findings: Causes of stress included violence, poverty, poor hygiene, neglect and poor care, maternal stress, and carer alcoholism. Consequences included a range of physical and mental adversity. Improved caregiving was seen as the most important prevention method. However, in contrast to previous research, stress was seen to affect older children, who have a better understanding of their environment, than younger infants. Taking saliva samples was straightforward. Mothers preferred to be helped by assessors to take these samples rather than doing it themselves. However, hair sampling was challenging. There are many cultural beliefs surrounding young children's hair and a child's first haircut is a ceremonial occasion: rates of refusal were high (four of 13 families refused). Sample size was adjusted accordingly. Interpretation: Measuring early life stress in the community is feasible and acceptable. Careful introduction in the community has achieved a 14% refusal rate to take hair samples despite major cultural barriers. These stress measures have been integrated into SPRING outcome assessments, which are being performed with a total of 1200 children. Each assessment is done over 2 days when a child reaches 1 year of age. 60 children are being assessed at home each week using salivary and hair cortisol measurments and questionnaires of environmental stressors developed using findings from our explanatory model. To our knowledge, SPRING is the first large child health intervention trial to include measures of early life stress and the first time that hair cortisol will be assessed in South Asian children. Funding: Wellcome Trust research training fellowship to SB (grant number 107818/Z/15/Z).